2018
DOI: 10.1016/j.expneurol.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The G2019S mutation in LRRK2 imparts resiliency to kinase inhibition

Abstract: The G2019S mutation in LRRK2 is one of the most common known genetic causes of neurodegeneration and Parkinson disease (PD). LRRK2 mutations are thought to enhance LRRK2 kinase activity. Efficacious small molecule LRRK2 kinase inhibitors with favorable drug properties have recently been developed for pre-clinical studies in rodent models, and inhibitors have advanced to safety trials in humans. Rats that express human G2019S-LRRK2 protein and G2019S-LRRK2 knock-in mice provide newly characterized models to bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 46 publications
21
64
0
Order By: Relevance
“…The existence of Rab10 in the tyrosine hydroxylase positive neurons controlling vision and proboscis movement argues that LRRK2 might indeed phosphorylate Rab10 directly. Thus our in vivo results both support the in vitro (biochemical and cell culture) data in which LRRK2 directly phosphorylates Rab10 (3)(4)(5)(6)(7)(8), but also suggest a separate pathway for LRRK2-G2019S action. Further, while Rab3 is also phosphorylated by LRRK2 in vitro (3), it did not synergise with LRRK2-G2019S in the visual assay, and was not detected in the MC neurons .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The existence of Rab10 in the tyrosine hydroxylase positive neurons controlling vision and proboscis movement argues that LRRK2 might indeed phosphorylate Rab10 directly. Thus our in vivo results both support the in vitro (biochemical and cell culture) data in which LRRK2 directly phosphorylates Rab10 (3)(4)(5)(6)(7)(8), but also suggest a separate pathway for LRRK2-G2019S action. Further, while Rab3 is also phosphorylated by LRRK2 in vitro (3), it did not synergise with LRRK2-G2019S in the visual assay, and was not detected in the MC neurons .…”
Section: Discussionsupporting
confidence: 86%
“…A number of studies highlighted a diverse range of >30 proteins that might be phosphorylated by LRRK2, suggesting it is a generalised kinase (2). However, several research teams have recently reported that LRRK2 is a more specific kinase, phosphorylating Rab GTPases (3)(4)(5)(6)(7)(8). However, it is not clear which of the more than 60 Rabs are actually phosphorylated in vivo.…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…S2A). These data suggest that pT73-Rab10 does not serve as a sensitive readout of LRRK2 kinase activity in the brain of this rat model, similar to prior reports in rodent brain (41). Instead, LRRK2 kinase activity was monitored by autophosphorylation at Ser1292 in brain tissue.…”
Section: Analysis Of Protein Levels and Kinase Activity Of Ad5-lrrk2 supporting
confidence: 70%
“…Third, the genetic analyses of LRRK2 kinase activity were complemented by pharmacological studies with PF-360, a potent and selective generation "3" LRRK2 inhibitor. PF-360 is highly potent with an in vivo IC50 of ~3 nM for LRRK2, and exhibits an improved selectivity profile, oral bioavailability and brain permeability compared to earlier generations of LRRK2 inhibitors (41,47). We demonstrate full inhibition of endogenous LRRK2 kinase activity in peripheral tissues and brain of our rat model with chronic in-diet dosing of PF-360 at 175 mg/kg chow.…”
Section: G2019s Mutation In Vivomentioning
confidence: 73%